Perbedaan Tekanan Darah berdasarkan Karakteristik Demografi dan Klinis pada Peserta Program Cek Kesehatan Gratis - Vivin Desy Kurniawati; Dwi Gayatri (Politeknik Baubau, 2026)
Introduction: Hypertension is a non-communicable disease that remains a global health challenge. This study aims to analyze differences in blood pressure (BP) based on demographic and clinical characteristics among adult participants of Free Health Check (Cek Kesehatan Gratis). Methods: This study employed a cross-sectional design involving 172 adult (≥18 years) CKG participants at Talangjambe Community Health Center Palembang City, South Sumatera Province from February to November 2025. Independent variabels were sex, age, body mass index, random blood glucose, and total cholesterol. Non-parametric Mann-Whitney U Test was used to analyze differences in BP. Results: The majority of participants were female (71,50%), aged 45-59 years (69,80%), non-obese (51,20%), with normal RBG (66,30%) and total cholesterol (84,30%). The mean systolic BP (SBP) was 138,62 ± 24,25 mmHg and diastolic BP (DBP) 85,07 ± 13,23 mmHg. Participants aged 45-59 years had higher BP compared to <45 years (SBP 142,78 ± 25,67; 95% CI 138,14-147,42 mmHg and DBP 86,68 ± 13,78; 95% CI 84,18-89,17 mmHg). Obese participants had higher DBP compared to non-obese (88,26 ± 14,40; 95% CI 85,14-91,39 mmHg). High RBG was associated with higher SBP compared to normal RBG normal (145,29 ± 27,25; 95% CI 138,13-152,46 mmHg). No differences in BP were found by sex or total cholesterol, nor in SBP by BMI, and DBP by RBG. Conclusion: Age, BMI, and RBG show differences in blood pressure in this population, therefore they can be considered as parameters for early detection of hypertension risk at community health centers.